2022
DOI: 10.3389/fpsyg.2022.838074
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the “Quality of Life in Life-Threatening Illness—Family Carer Version” (QOLLTI-F) in Persian-Speaking Carers of COVID-19 Patients

Abstract: BackgroundMeasuring family caregivers’ quality of life plays a significant role in improving the quality, efficiency, development, and provision of efficient services for patients with COVID-19. As a result, evaluating the quality of life requires the use of valid and reliable measures that are culturally appropriate. This study was conducted to determine the psychometric properties of the Persian version of the Quality of Life in Life-Threatening Illness–Family Carer Version (QOLLTI – F) in patients with COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…All 16 items of the original QOLLTI-F were retained in the QOLLTI-F-CV, but our study has revealed a stable three-factor solution. This is consistent with the results of the study by Arias-Rojas et al (2021) and Fereidouni et al (2022) . Although some entries have a slightly different distribution of domains, we conducted PA to determine the number of factor extraction, which is more robust than the K1 method used by O’Conner (2000) , Mu and Gu (2011) , and Schur et al (2014) .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…All 16 items of the original QOLLTI-F were retained in the QOLLTI-F-CV, but our study has revealed a stable three-factor solution. This is consistent with the results of the study by Arias-Rojas et al (2021) and Fereidouni et al (2022) . Although some entries have a slightly different distribution of domains, we conducted PA to determine the number of factor extraction, which is more robust than the K1 method used by O’Conner (2000) , Mu and Gu (2011) , and Schur et al (2014) .…”
Section: Discussionsupporting
confidence: 93%
“…Although some entries have a slightly different distribution of domains, we conducted PA to determine the number of factor extraction, which is more robust than the K1 method used by O’Conner (2000) , Mu and Gu (2011) , and Schur et al (2014) . Since ESEM has the advantage in terms of exploring factor structure flexibly and verifying the factor model systematically ( Liu and Liu, 2013 ), it can make the model structure more consistent with the actual situation and the fitting more robust, compared with EFA which is used by Schur et al (2014) , Arias-Rojas et al (2021) , and Fereidouni et al (2022) . The results showed that the three-factor structured model fitted the empirical data well, as indicated by the fit indices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations